2020
DOI: 10.1101/2020.08.27.20183178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is genetic diversity of Plasmodium falciparum suggestive of malaria endemic zone in West Africa? An attempt to respond by a cross-sectional comparative study between Senegal and Nigeria

Abstract: Background: Characterization of malaria parasite populations in different endemic settings (from low to high) could be helpful for ascertaining the progress of malaria interventions in endemic settings. The present study aims to compare Plasmodium falciparum parasite population structure between two West African countries with very different level of endemicity using P. falciparum allelic polymorphic markers: msp1 and msp2. Methods: Parasite genomic DNA was extracted from 187 dried blood spot collected from c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Given that P. falciparum in vitro adaptation could also be influenced by the number of parasite clones present in a given isolate, our genotyping analysis revealed that all P. falciparum clinical isolates used in this study presented multiple parasite clones, with an overall MOI of 4.4, which is slightly higher than previously reported in data from Burkina Faso 20 , Ghana , Republic of Congo 22 , Nigeria and Senegal . However, the predominance of K1 and 3D7 allelic families of msp1 and msp2 reported here is in agreement with previous reports from Burkina Faso 20,24 , Ethiopia 25 , Ghana 26 , Nigeria and Senegal 23 , but contrary to studies from Uganda and Sudan which reported the predominance of RO33 and FC27, respectively for the two genes 25,27 .…”
Section: Discussionsupporting
confidence: 92%
“…Given that P. falciparum in vitro adaptation could also be influenced by the number of parasite clones present in a given isolate, our genotyping analysis revealed that all P. falciparum clinical isolates used in this study presented multiple parasite clones, with an overall MOI of 4.4, which is slightly higher than previously reported in data from Burkina Faso 20 , Ghana , Republic of Congo 22 , Nigeria and Senegal . However, the predominance of K1 and 3D7 allelic families of msp1 and msp2 reported here is in agreement with previous reports from Burkina Faso 20,24 , Ethiopia 25 , Ghana 26 , Nigeria and Senegal 23 , but contrary to studies from Uganda and Sudan which reported the predominance of RO33 and FC27, respectively for the two genes 25,27 .…”
Section: Discussionsupporting
confidence: 92%
“…Our fndings suggest that K1 and 3D7 parasite strains are the common genotypes circulating in the study region. A similar observation was recorded in another area of the country (for the msp2 gene) [18], Nigeria and Senegal [38,39].…”
Section: Discussionsupporting
confidence: 85%